Jasminaldehyde production without the use of solvents by employing solid-acid catalysts based on a double metal cyanide: Investigating the Catalytic Activity of Fe-Zn Double Metal Cyanide Catalysts in Solvent-free Synthesis of Jasminaldehyde (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Solvent-free synthesis of jasminaldehyde via liquid phase condensation of benzaldehyde and 1-heptanal at 433 K is investigated, with a focus on the catalytic activity of Fe-Zn double metal cyanidecatalysts. Under ideal reaction circumstances, 1-heptanal is converted to jasminaldehyde with a selectivityof 77. Condensation is facilitated in Fe-Zn double metal cyanide because to the presence ofcoordinatively unsaturated Zn2+ in the framework of the compound. Selectivity of jasminaldehyde wasinvestigated by varying the complexing and co-complexing agent, catalyst amount, benzaldehyde to 1-heptanal molar ratio, and temperature.